Study of the Effectiveness of Poverty Reduction Programs; an Analytic Hierarchy Process Approach - Andi Faisal Anwar; Rini Indah Sari (Bulletin of Economic Studies (BEST), 2021)
The budget allocation for poverty alleviation is getting bigger from time to time. However, the poverty rate did not change significantly. This study aims to determine the effectiveness of poverty programs that have been initiated by the government, through programs (KUBE, PANSIMAS, BUNDES, PNPM, and P2KP), which are believed to improve poverty alleviation efforts in Manyampa Village, Ujung Loe District, Bulukumba Regency. The research method used in this research is quantitative research, with the AHP (Analytic Hierarchy Process) analysis method. Data collection techniques were obtained from questionnaires or primary data sources, while secondary data were obtained from reports from BPS South Sulawesi, BPS Bulukumba, District Offices and related agencies in Bulukumba Regency. The novelty of this study is to explore further and evaluate what programs are quite effective in reducing poverty rates, with the help of expert choice with a consistency test. The results of this study indicate that in poverty alleviation efforts, the P2KP program is the most effective in reducing poverty with small business empowerment-based programs, while from community empowerment-based programs, the PANSIMAS program is more consistent than other programs in poverty alleviation efforts. P2KP and the PANSIMAS program each got a score of 0.02<0.1. It can be interpreted that the Inconsistency ratio <0.1 (the maximum limit) is also tested to be consistent, it's just that the achievement is lower than other programs. The implication of this research is that the local government needs to further evaluate ineffective poverty alleviation programs so that budget misallocations do not occur and are able to accelerate effective poverty alleviation programs that have been running. Keywords: Poverty, Program, Efectiveness